Models of Education Financing and their Impact on Students Performance - Kostrhoun, Tomáš; Nikolovová, Pavla, 1982-; Čermáková, Klára; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2016)
This thesis focuses on the influence of private enrolment in OECD countries on education performance exhibited by students. In my work I analyse panel data portraying annual status of economy and education system in 34 OECD countries from 2000 till 2014. In the first part, I present the historical evolution of the approach to education in terms of public and private goods, in the second part, I provide an overview of related literature that provides a cornerstone for my practical part. In my practical part, I investigate the influence of economic background of OECD countries, educational system and rate of private enrolment on students´ performance. The conclusion of my models did not confirm my hypothesis of beneficial influence of private enrolment on performance. Private enrolment is insignificant in majority of models. Reasoning for this phenomenon may be different approach of students to private education. In some countries, private institutions are perceived as complement and in some as a substitute to good cognitive abilities.
Vedoucí práce: Pavla Vozárová
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2016
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2016
Způsob přístupu: Internet
Keywords: ekonomie [obor bakal. práce]; bakalářské práce; bachelor's theses